Nutritional Status of Elementary School-Age Children in Oransbari About Cognitive and Motoric Ability - Pratiwi, Yeni Aulia; Bedjo, Muhammad Ramadhan; Hazwia, Hazwia; Ijie, Daniela; Kawulur, Elda Irma Jeanne Joice (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2025)
One of the phenotypic variations in humans to adapt to environmental conditions is physical growth. One of the impacts of environmental pressure on children's growth is malnutrition. This research aims to assess the association of nutritional status with cognitive abilities and motor skills in elementary school-age children in Oransbari, South Manokwari, West Papua. Cross-sectional design research was carried out on children aged 6–12 years from two primary schools in January- June 2023. Semistructured interviews guided by a questionnaire were carried out to collect data on cognitive and motoric abilities. Body height and body weight were measured to assess the nutritional status. Our research showed that nutritional status was mostly a normal category, while stunting, severe stunting, and thinness which refers to undernutrition were quite low. Undernutrition tendency in Papuan children was higher than in non-Papuan children, with the severely stunted 2.44%:0.83% between Papuan and non-Papuan and thinness at 7.32%:5.83%. Expectably stunted category non-Papuan showed quite high than Papuan (3.33%:2.44%). In contrast, the percentages of thinness and obesity which refer to overnutrition were quite high in non-Papuan with values of 14.0% and 16.6% respectively. The chi-square test showed that the malnutrition category was not related to cognitive and motor skills (P-value <0.05).